Removal Of Ammoniacal Nitrogen And Suspended Solids In Sewage Wastewater By Using Ferrous Sulfate In Coagulation Process Via Zeta Potential And Particles Size Measurements - Kamarzaman, Fatin Farhana (Universiti Sains Malaysia, 2018)
A comprehensive sewage characterization was conducted to further understand the nature of sewage generated in domestic and commercial areas. It was revealed that the characteristic sewage in domestic areas resembled the typical sewage characteristic reported globally. In the first phase of this study, to characterize the initial wastewater characteristics for each sample and wastewater quality, laboratory work were carried out included ammoniacal nitrogen (NH3-N), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS) and e.coli. Next in the second phase of this study, to analysis and measurements of the average zeta potential and particles size as a function of pH were carried out separately for the sewage wastewater and the selected coagulant which is the selected of coagulant was ferrous sulfate hydrated, FeSO4.7H2O. Based on the results, the optimum pH range was predetermined which is pH 2 and pH 8. This is subsequently followed through by observing the aggregation and disaggregation behaviour of the size particles in the sewage wastewater due to the interaction with the coagulant as the function of the coagulant concentration. Finally, a jar test was conducted to validate the preliminary findings by evaluating selected pollutant removal in percentage values (%). It was reported that for pH 2, percentage of pollutant removal for BOD5, COD and TSS were 86.0%, 88.9% and 73.5% respectively which higher compared to pH 8 that obtained of 59.3%, 92.1% and 66.7% respectively. However, for concentration of NH3 –N and e.coli at pH 2 were obtained of 33.9% and 66.1% respectively while pH 8 is about 21.9% and 64.1% respectively. Hence, the objective to calculate the percentage of pollutant removal based on the predetermined optimum pH which is pH 2 and pH8 and coagulant dosage range has been achieved.